Challenges in assessing response of oesophageal cancer to neoadjuvant therapy, and the potential of composite PET-CT and multimodal metrics. - Findlay, J; Bradley, K; Gillies, R; Maynard, N; Middleton, M (AME Publishing Company, 2017)
We read with interest Dr Włodarczyk and Professor Kużdżał’s appraisal of the potential for composite positron emission tomography-computed tomography (PET-CT) metrics to improve the assessment of oesophageal cancer to neoadjuvant therapy, in particular that of a new metric we recently described: metabolic nodal response (mNR)